UPAYA MENINGKATKAN KESADARAN MASYARAKAT UNTUK MENGURANGI ANGKA STUNTING OLEH KKN PMD UNRAM DI DESA KAYANGAN DENGAN PEMBERIAN OLAHAN PUDING KELOR - Zahra, Nisrina; Thalita, Deandra Alma; Irawan, Hensen Dadang; Nurikhlastari, Astriyani; Azamy, Abdika Thariqul; Yamin, Muhammad; Artiwi, Neni Asti; Khairani, Sri; Ihsani, Nur; Iman, Zahratul; Sili, Eduardus Bayo (Jurnal Wicara, 2024)
Kuliah Kerja Nyata (KKN) PMD is a form of student service as participants who go directly to the community and are continuously guided by field supervisors in educating the target village community, especially in health. The village that is the focus of this KKN is Kayangan Village, Kayangan District, North Lombok Regency. Kayangan Village is a village supported by good natural resources to improve the development and welfare of the community. The natural resources consist of agricultural land and forest land. The kayangan village government has never escaped the activity of fostering the community to have a healthy lifestyle. this is done during posyandu activities. However, from the data obtained from the village head, the puskesmas and the posyandu cadres of kayangan village, there were 20% affected by stunting in 2023 and it is hoped that this figure will decrease in 2024. In realizing this hope, we from the Kayangan Village KKN group carried out 4 work programs with 1 main work program, namely socialization about health and the use of moringa leaves in an effort to realize a stunting-free generation and 3 additional work programs including posyandu, gymnastics, and gotong royong and distribution of moringa pudding carried out during posyandu activities.